Monitoring Human Movement in Building Using Bluetooth Low Energy - Hoa, Jeffrey; Soewito, Benfano (CommIT (Communication and Information Technology) Journal, 2018)
In recent years, smartphones have become more popular. Along with the increasing number of smartphone users, more features are requested by the users which can be used to solve their daily life problems. One of the most popular applications is related to location-based detection. Almost all smartphones have a feature of Global Positioning System (GPS). It can help users to go from one place to another place without getting lost by connecting to Google Map. However, there are some limitations to the GPS. When the GPS is used inside a building, it is difficult to search where the users are located, on which floor or room they are, and how to access the room inside the building. It is because GPS cannot show the user which level or room location the users are currently at. One of the possible solutions is using an Indoor Positioning System (IPS) which can detect an object or person inside a building by producing some signals that can be received by smartphones. This research aims to develop an application to monitor the movement of humans inside a building with low cost and low energy by using Android smartphones as the medium. It can get the coordinate of location by using Bluetooth Low Energy (BLE) beacon inside the building. It can also be used to detect multiple users in the same room.